Effectiveness of the Combination of the Birthing Ball Method and Finger Reflexology To reduce labor pain in women giving birth during the first active phase In the Maternity Room of the Betun Health Center - lucia claritha leki; Yulida Ti’ani (Master of Public Health Program Universitas STRADA Indonesia, 2022)
The birth process is identical to the pain that will be experienced. Pain during labor is a physiological process. The high incidence of pain in mothers giving birth, 15% experience mild pain, 35% with moderate pain, 30% with severe pain and 20% of labor is accompanied by very severe pain. This causes birth mothers to want a birth process with minimal pain. There are many ways to reduce labor pain, one of which is using the birthing ball method and finger-held reflexology. The aim of this study was to determine the effectiveness of the combination of the birthing ball method and finger-held reflexology to reduce labor pain. This research is quantitative research with a research design including experimental research. This research is included in the Quasi Experimental type of research with a pre test and post test control group design. The sample in this study was taken using a purposive sampling technique and divided into two groups, one group acting as the treatment group and the other acting as the control group. The research was conducted in the maternity room of the Betun Community Health Center. The results of the study showed that there was a decrease in the degree of pain in the intervention group from a moderate pain scale to a mild pain scale of 30% as proven by the Wilcoxon test. earned value asymp say.(2 tailed)=0.020 (<0.05), then statistically it shows the effectiveness of the combination of the birthing ball method and handheld finger reflexology to reduce labor pain in mothers during the first active phase. From the results above, it can be concluded that there is effectiveness in using a combination of the birthing ball method and finger-held reflexology to reduce labor pain in mothers giving birth during the first active phase in the Betun Community Health Center Maternity Room.